Information on elemental and ionic components obtained from aircraft engine smoke number filter sample - Saitoh, Katsumi; Spirig, Curdin; Edebeli, Jacinta; Anet, Julien G.; Kikuchi, Yohei; Toyama, Sho; Miwa, Misako; Matsuyama, Shigeo; Fushimi, Akihiro; Takegawa, Nobuyuki (European Journal of Applied Sciences, 2021)
To extract information on elemental and ionic species components and particulate matter (PM) characteristics from smoke number (SN) filter paper, we were performed elemental analysis by micro-PIXE and ion component analysis by ion chromatography. As a result of elemental and ionic species component analysis of the SN filter, information on the chemical composition of jet engine exhaust PM was obtained. Regarding the SN filter, jet engine exhaust PM was collected for each difference in engine thrust of various aircraft engines at aircraft turbine engine test cells around the world. By periodically analyzing the chemical composition of the SN filter, it is possible to identify the characteristics of the emission PM of each aircraft engine and the transformation of the chemical composition of the emission PM with the passage of time. This was thought to lead to the evaluation of jet engines.